INFLUENCE OF LIPOSUCTION OF LARGE VOLUME ON SYSTEMIC AND LUNG CIRCULATION, OXIGENATED LUNG FUNCTION - I. P. Nikolaeva; A. S. Kapranova; V. B. Popova; A. N. Lodyagin; T. A. Frolova (Вестник хирургии имени И.И. Грекова)
The authors measured the changes of hemodynamics in 72 patients. It was also estimated a blood oxygenation and volume of liquid sectors of the organism in different degree of obesity before and after liposuction of the large volume. It was shown, that this operation facilitated to an improvement of respiratory lung function due to changes of pulmonary circulation.